The Influence of Work Environment and Work Motivation on Employee Performance at PT. Valdo International Central Jakarta - Suwanto Suwanto (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The purpose of this study was to determine the effect of work environment and work motivation on employee performance at PT. Valdo International in Central Jakarta. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 90 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that the work environment has a significant effect on employee performance with a determination coefficient value of 50.8% and the hypothesis test is obtained t count > t table or (9.525 > 1.987). Work motivation has a significant effect on employee performance with a determination coefficient value of 37.9% and hypothesis testing obtained t count > t table or (7.334 > 1.987). Work environment and work motivation simultaneously have a significant effect on employee performance with the regression equation Y = 6.538 + 0.492X1 + 0.345X2. The coefficient of determination is 58.6% while the remaining 41.4% is influenced by other factors. Hypothesis testing obtained F count > F table or (61.475 > 2.710).